SİYASAL-SOSYAL GÖRÜŞLERİ VE DİNİ YÖNÜYLE AFGANİ1 (Son Bir Umut: İslam Birliği) - Muammer Esen (İslami İlimler Dergisi)
As a religious scholar, al-Afghani, who is the most prominent Pan-Islamist figure of the modern history of Islam with a robust anti-imperialistic stance, has been a subject of controversy in terms of his life, personality, nationality and school of thought to which he belonged. He traveled to many countries, especially the significant political and cultural centers of the Muslim world, in order to warn Muslims of his time against the imperialist powers. Emphasizing the importance of a sound understanding of religion cleansed from superstitions, al-Afghani thought that a religion founded upon a sound basis of wisdom is centered around human happiness. And in his view, good deeds result from a genuine faith. Although he thinks that the creedal sects (schools of thought) are needed for human beings, he disapproves of their being a cause of disintegration by being transformed into a religion. Ijtihad, independent religious judgment, has a crucial role in his thought.